The Association between Corporate Governance and Executive Compensation of China Information Technology Listed Company - Fan, Ruiting (2020)
The dissertation is of great significance since China's information technology industry has made contributions to China's overall economic growth. However, unreasonable CEO compensation have always existed and few studies in Chinese literature focus on the information technology industry. In addition, scholars pay more attention to the link between corporate performance and CEO compensation. Therefore, this dissertation intends to evaluate the impact of corporate governance on executive compensation in information technology.